Mass politics : studies in political sociology / edited by Erik Allardt and Stein Rokkan ; with a foreword by Seymour M. Lipset - Allardt, ErikRokkan, SteinLipset, Seymour Martin
En el prefacio: '...brings together papers and reports from four conferences organized under the auspices of the Committee on Political Sociology...' | Bibliografía y notas. Índice.